Situational Modeling - the Effective Tool for Strategic Planning and Management - Valery Leonidovich Makarov; Albert Raufovich Bakhtizin; Elena Davidovna Sushko (Управленческое консультирование)
In the article the short description of two agent - oriented models entering an expected complex of the situational room of CEMI of the Russian Academy of Sciences - the powerful instrument of support of strategic planning and management is given.